Heritage for Development, Multiethnic Communities, and the Case of Butrint National Park on the Albanian-Greek Border - Phelps, Dana (Ex Novo: Journal of Archaeology, 2016)
The case study presented in this paper is an account of six months of ethnographic fieldwork that I conducted between 2010 and 2013 in the villages within the UNESCO World Heritage site of Butrint National Park, located on the Albanian-Greek border. My ethnography reveals the particularly complex tangle that exists between development and heritage projects in transitioning countries such as Albania, which is re-positioning its governance within a neoliberal framework. The research takes an anthropological approach to investigate how the “heritage for development” projects at Butrint National Park are affecting the local community and distressing local power relations and social inequalities, while at the same time are instilling a sense of place for many of these communities that have relocated or were forced from their homes during the post-communist period as a result of confusion over land ownership. This case study demonstrates that while sustainable heritage practices are often overpowered by neoliberal agendas, heritage repurposed towards development has real and powerful effects on the communities connected to the site. In this paper I argue that we need anthropologically informed studies that give due attention to the realities of the communities connected to the site in order to reveal how sustainable heritage policies that are not set up to protect the community can have detrimental effects on the locals, including reinforced structural inequality, marginalization of minorities, and divisions among communities.